2009
DOI: 10.4161/cbt.8.13.8890
|View full text |Cite
|
Sign up to set email alerts
|

Genes involved in regulation of stem cell properties: studies on their expression in a small cohort of neuroblastoma patients

Abstract: Cancer stem cells have been isolated from many tumors. Several evidences prove that neuroblastoma contains its own stem cell-like cancer cells. We chose to analyze 20 neuroblastoma tumor samples in the expression of 13 genes involved in the regulation of stem cell properties to evaluate if their misregulation could have a clinical relevance. In several specimens we detected the expression of genes belonging to the OCT3/SOX2/NANOG/KLF4 core circuitry that acts at the highest level in regulating stem cell biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Melone et al detected the expression of Oct4 in NB cells and tissue samples, but Sox2 expression was not found (29). Gomez-Mateo et al evaluated the expression and clinical significance of Sox2 in NB using immunohistochemical staining and found that high Sox2 protein levels correlate to aggressive disease, indicating that Sox2 protein levels may be an important prognostic indicator of NB (30).…”
Section: Discussionmentioning
confidence: 99%
“…Melone et al detected the expression of Oct4 in NB cells and tissue samples, but Sox2 expression was not found (29). Gomez-Mateo et al evaluated the expression and clinical significance of Sox2 in NB using immunohistochemical staining and found that high Sox2 protein levels correlate to aggressive disease, indicating that Sox2 protein levels may be an important prognostic indicator of NB (30).…”
Section: Discussionmentioning
confidence: 99%
“…BE(2)-C cells have a typical I-type phenotype, and show consistent morphological and biochemical responses to differentiation-inducing agents (12,23,24). We further established stable cell lines that overexpressed and had downregulated expression of SOX2 by infecting BE(2)-C cells via lentiviral transduction vectors, following which we explored the functions of SOX2 in cell proliferation, clonogenicity, tumorigenicity and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…OCT4 has been used as a cell marker in NB to identify progenitor cells (12)(13)(14)(15)(16)(17). Our study showed that the expression levels of OCT4 strongly correlated with the stemness of NB I-type cells BE (2)-C. High expression of OCT4 increases grades and correlates with tumor progression and malignancy in glioma, a nervous system malignant tumor (8).…”
Section: Discussionmentioning
confidence: 62%
“…Recent findings demonstrated that OCT4 also plays an oncogenic role and is expressed in some cancer stem cells (8)(9)(10)(11). Furthermore, previous studies detected the expression of OCT4 in NB primary samples, metastatic bone marrow aspirates, cell lines, and OCT4 is facilitated to identify NB cancer stem cells as the stemness gene (12)(13)(14)(15)(16)(17). OCT4 is proved to have a potential role in maintaining NB cancer stem cell niche localized in the hypoxic zones of the solid tumors in vivo (12) and is used for identification of tumor-derived endothelial cells as a putative marker (17).…”
Section: Introductionmentioning
confidence: 99%